Parkinson’s Disease: A Nanotheranostic Approach Targeting Alpha-Synuclein Aggregation - Zoey, Fong LaiGuan; Palanivel, Mathangi; Padmanabhan, Parasuraman; Gulyás, Balázs (Frontiers in Cell and Developmental Biology, 2021)
Parkinson’s disease (PD) is one of the most common neurodegenerative disorders that is implicated in aging populations. As numerous developed nations are experiencing progressively aging populations today, there is a heightened propensity for the occurrence of PD cases. Alpha-synuclein (α-syn) aggregation has been considered to be the pivotal mechanism leading to PD pathogenesis. Thus, early diagnostic and therapeutic strategies targeting the misfolded α-syn protein can potentially improve the prognosis of PD. With rapid advancements in nanotechnology in the last decade, effective solutions to various neurodegenerative and oncological diseases have been suggested. This review will explore the current innovations in nanotechnology that target the α-syn aggregation pathway, and reinstate the promise they hold as effective early diagnostic and therapeutic solutions to PD.